2004
DOI: 10.1016/j.jvs.2003.10.018
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative complications and early outcome after endovascular and open surgical repair of abdominal aortic aneurysms

Abstract: Both elective OR and EVAR can be performed with low mortality, but cardiac and pulmonary complications are less frequent and less severe after EVAR. The tradeoff of EVAR is a higher rate of graft-related complications, with more reinterventions and a lower graft patency rate at 1 year. These results should be considered before EVAR is offered to patients with AAA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
79
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 21 publications
4
79
0
6
Order By: Relevance
“…The advantage of EVAR over open AAA repair is that it is considerably less invasive and associated with a lower initial mortality rate and morbidity rates. [35][36][37] The main disadvantage of EVAR is that the repair is less stable with a substantially higher rate of late AAA-related complications including endoleak, graft displacement, stent fracture and even AAA rupture. 35,38 There have been a number of comparative studies between open AAA repair and EVAR.…”
Section: Open or Endovascular Repairmentioning
confidence: 99%
“…The advantage of EVAR over open AAA repair is that it is considerably less invasive and associated with a lower initial mortality rate and morbidity rates. [35][36][37] The main disadvantage of EVAR is that the repair is less stable with a substantially higher rate of late AAA-related complications including endoleak, graft displacement, stent fracture and even AAA rupture. 35,38 There have been a number of comparative studies between open AAA repair and EVAR.…”
Section: Open or Endovascular Repairmentioning
confidence: 99%
“…Some complications occur during or soon after the procedure, whereas others are only noticed during graft surveillance (Table 4). 34 A study by Ohki et al 35 analyzed complication and death rates within 30 days of EVAR and found the major complication and death rates were 17.6% and 8.5%, respectively. This remains an active and important area of EVAR research, and standards have been developed to facilitate reporting of endovascular abdominal aortic repair complications.…”
Section: Complicationsmentioning
confidence: 99%
“…Current literature data indicate a clear trend toward reduction of mortality rate in patients from high perioperative risk groups due to progress in surgical technique and anesthesiology, associated with AAA treatment. surgical trauma, longer duration of the procedure and bigger blood loss (36). In 1996 Lawrence et al published data that indicated that pulmonary complication rate after abdominal surgical procedures was similar to cardiac complication rate (37).…”
Section: Risk Of Treatment Of Asymptomatic Aaamentioning
confidence: 99%